2019
DOI: 10.1021/acsomega.9b00148
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Biocarbons with Controlled Micropores and Mesopores Derived from Kapok Fruit Peels for High-Performance Supercapacitor Electrodes

Abstract: Hierarchical microporous and mesoporous biocarbons derived from kapok fruit peels were prepared by a two-step method. First, a carbon precursor was prepared from the kapok fruit peels by precarbonization at lower temperature, and then it was activated at a higher temperature with KOH as an activation agent. Micropores and mesopores of the biocarbons were controlled by adjusting the mass ratio of KOH to the carbon precursor. Especially, the biocarbon AC4 that was prepared with a KOH/carbon precursor mass ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Both AC and CC showed a combination of micropores and mesopores in a range from 1.53 to 1.91 nm and from 2.16 to 15.13 nm, respectively, which agreed with the nitrogen adsorption–desorption isotherms. The presence of both micropores and mesopores suggested that AC is suitable for high-capacity ion and charge storage for supercapacitors as micropores support the charge storage process while mesopores allow effective ion transfer from the electrolyte. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both AC and CC showed a combination of micropores and mesopores in a range from 1.53 to 1.91 nm and from 2.16 to 15.13 nm, respectively, which agreed with the nitrogen adsorption–desorption isotherms. The presence of both micropores and mesopores suggested that AC is suitable for high-capacity ion and charge storage for supercapacitors as micropores support the charge storage process while mesopores allow effective ion transfer from the electrolyte. , …”
Section: Resultsmentioning
confidence: 99%
“…The presence of both micropores and mesopores suggested that AC is suitable for high-capacity ion and charge storage for supercapacitors as micropores support the charge storage process while mesopores allow effective ion transfer from the electrolyte. 30,31 3.2. Characterizations of CDs.…”
Section: Synthesis and Characterization Of Acmentioning
confidence: 99%
“…Similarly, kapok fiber has been utilized as micro-tube biomaterial or biotemplate for electrodes in fuels cells or batteries [74][75][76][77] and supercapacitor [78][79][80] . Synthesis using simple hydrothermal method followed by calcination at high temperature and inert atmosphere was the method employed to produce an electroactive hybrid composite.…”
Section: Kapok Fiber As Biomass Materials For Catalyst and Electrodesmentioning
confidence: 99%
“…[23,24] Possible steps include developing a hierarchical pore framework through a combination of relatively equal micro/meso distributions. [25] This strategy has been reported to be successful by Zhang et al (2022) which synthesized pecan shell-based activated carbon through KOH impregnation. [23] They provided significantly detailed information regarding the importance of considering the micro/meso ratio of activated carbon for electrochemical double-layer capacitor applications.…”
Section: Introductionmentioning
confidence: 99%